Cortical entrainment to continuous speech: functional roles and interpretations - Ding, Nai; Simon, Jonathan Z. (Frontiers in Human Neuroscience, 2014)
Auditory cortical activity is entrained to the temporal envelope of speech, which corresponds to the syllabic rhythm of speech. Such entrained cortical activity can be measured from subjects naturally listening to sentences or spoken passages, and provides a reliable neural maker of online speech processing. A central question still remains to be answered about whether cortical entrainment is more closely related to speech perception or non-speech-specific auditory encoding. Here, we review a few hypotheses about the functional roles of cortical entrainment, e.g., encoding acoustic features, parsing syllabic boundaries, and selecting sensory information in complex listening environments. It is likely that speech entrainment is not a homogeneous response and these hypotheses work for speech entrainment generated from different neural sources. The relationship between cortical entrainment and speech intelligibility is also discussed. A tentative conclusion is that theta-band entrainment (4-8 Hz) encodes speech features that are critical for intelligibility while delta-band entrainment (1-4 Hz) is related to the perceived, non-speech-specific acoustic rhythm. To further understand the functional properties of speech entrainment, a splitter’s approach will be needed to investigate (1) not just the temporal envelope but what specific acoustic features are encoded and (2) not just speech intelligibility but what specific psycholinguistic processes are encoded by entrained cortical activity. Similarly, the anatomical and spectro-temporal details of speech entrainment need to be taken into account when investigating its functional properties.